Anatomic and Nonanatomic Double-Bundle Anterior Cruciate Ligament Reconstruction: An In Vivo Kinematic Analysis. (March 2014) - Zaffagnini, Stefano; Marcheggiani Muccioli, Giulio Maria; Signorelli, Cecilia; Lopomo, Nicola; Grassi, Alberto; Bonanzinga, Tommaso; Nitri, Marco; Marcacci, Maurilio
Background: There have been no direct in vivo biomechanical comparisons performed between an anatomic double-bundle (ADB) and a nonanatomic double-bundle (NADB) anterior cruciate ligament (ACL) reconstruction. Hypothesis: There are differences in kinematic outcomes between ADB and NADB ACL reconstruction techniques. Study Design: Controlled laboratory study. Methods: Twenty-six consecutive patients (mean age, 30 years; range, 18-32 years; 23 men, 3 women; 17 right knees, 9 left knees) with an isolated ACL injury were included in the study. The first 13 consecutive patients underwent NADB reconstruction (combination of a single-bundle and an over-the-top reconstruction), and the following 13 consecutive patients were treated with an ADB approach (using 2 tibial tunnels and 2 femoral tunnels placed in the center of the native femoral and tibial insertion sites). Grafts were pretensioned at 80 N and secured with cortical fixation systems under manual maximum force tension. Standard clinical laxity and pivot-shift tests were quantified at time zero before and after ACL reconstruction by means of a surgical navigation system dedicated to kinematic assessment; displacement of the medial and lateral compartments during the tests was also analyzed. Results: The ADB-reconstructed knees showed a larger preoperative-to-postoperative difference in anterior-posterior tibial plateau displacement of the medial and lateral compartments when compared with the NADB-reconstructed knees during the internal-external rotation test at 30° of flexion ( P < .050). No other significant differences in laxity or pivot-shift values were noted. The mean surgical time for ADB reconstruction was significantly higher than that for NABD reconstruction (62 ± 13 and 43 ± 10 minutes, respectively; P < .0001). Conclusion: Results showed a greater anterior-posterior translation of both compartments during the rotational passive laxity test in the ADB reconstruction group or overconstraint caused by the NADB technique. The 2 analyzed double-bundle ACL reconstructions did not show any significant quantitative difference in isolated anterior-posterior laxity and pivot-shift phenomenon at time zero. Clinical Relevance: Nonanatomic double-bundle ACL reconstruction can control anterior-posterior laxity and the pivot-shift phenomenon as well as ABD ACL reconstruction.